Catalytic hydrolysis of corncob for production of furfural and cellulose-rich solids: Product characterization and analysis. (January 2023) - Yao, Bang; Kang, Qinhao; Fu, Jie; Liu, Yang; Ao, Wenya; Wang, Long; Jiang, Zhihui; Zhang, Tianhao; Song, Yongmeng; Deng, Zeyu; Siyal, Asif Ali; Dai, Jianjun
Abstract: Experiments were carried out to investigate cellulose and furfural from catalytic hydrolysis of corncob. This process improved the comprehensive utilization of hemicellulose and cellulose in biomass resources. Influence of factors (temperature, reaction time, concentration of catalysts, liquid to solid ratio (LSR)) on hydrothermal characteristics, furfural yield, properties and retention of cellulose were investigated through orthogonal and parameter tests. Acetic acid (6 wt%) and FeCl3 (40 mM) achieved the highest furfural yield (47.60%) and relatively high cellulose retention ratio (71.84%) at 180 °C, 45 min, and 3 mL/g of LSR. While AlCl3 and citric acid obtained low furfural yield and the lowest cellulose retention ratio (8.38%). Furfural was dominant in distillated organics (GC-MS areas ≥97.9%), by contrast furfural, 5-hydroxymethyfurfural and vanillin were main organics in residual liquors. The peak of furfural yield switched to shorter reaction time as temperature increased. Combination of AlCl3 with acetic acid and citric acid accelerated cellulose degradation. NaCl inhibited furfural yield and promoted lignin decomposition. Higher temperature and greater concentration of FeCl3 contributed to reduced crystallinity of cellulose during hydrothermal treatment. Graphical abstract: Image 1 Highlights: Higher temperature and added FeCl3 contributed to reduced crystallinity of cellulose. AlCl3 with acetic acid and citric acid accelerated cellulose degradation. Acetic acid and FeCl3 achieved 47.60% furfural yield and 71.84% cellulose retention. NaCl inhibited furfural and promoted lignin decomposition. Furfural, 5-hydroxymethylfurfural and vanillin were three major hydrolysates.